Predicting Factors of Symptoms among Persons Suspected of Acute Coronary Syndrome in Emergency Department, Secondary Hospital - Karaket, Anusorn; bunklai, ketnarin; Talerd, Wannachart; Wetsasin, Kanokwan; Phetcharak, Kannika; Demile, Ladapha; Peaschpunpisal, Chuanchom (Princess of Naradhiwas University Journal, 2025)
This predictive correlational study aimed to identify factors that predict patient-reported symptoms of acute coronary syndrome (ACS) individuals presenting with suspected ACS at the emergency department of secondary hospital, A purposive sample of 419 individuals aged 35 years and older with suspected ACS was selected. Data were collected through interviews using a questionnaire, which included demographic information, a 15-symptom checklist, and a clinical data form. Descriptive statistics, Chi-Square, and binary logistic regression were employed for data analysis. The results revealed that 62.53% of the participants developed ACS. Chest pain (OR=1.924, 95% CI 1.196–3.096, p=.007), shortness of breath (OR=2.237, 95% CI 1.229–4.072, p=.008), upper xiphoid and abdominal pain (OR=0.275, 95% CI 0.133–0.567, p<.001), and weakness or dizziness (OR=2.650, 95% CI 1.367–5.140, p=.004). Collectively, these factors predicted ACS with statistical significance at p <.05 and predicted the occurrence of ACS by 66.80%. The findings suggest that healthcare providers should have prioritized early screening and monitoring of ACS, particularly in patients presenting with chest pain, shortness of breath, abdominal discomfort, and weakness or dizziness, to facilitate timely diagnosis, enhance treatment outcomes, and lower the risk of complications from delayed recognition.